2021
DOI: 10.26650/ibr.2021.51.0073
|View full text |Cite
|
Sign up to set email alerts
|

Price Sensitivity Measurement: A Yield Management Approach

Abstract: The purpose of this paper is to investigate and identify the potential revenue losses, at price points determined by price sensitivity measurement, between actual revenue and potential revenue that can be gained, in terms of yield management. A case study was carried out in a 5 star hotel business in Aydın, Turkey. In the study, a questionnaire was conducted to determine price resistance levels, price threshold limits, price sensitivity levels and price perceptions based on the room quality perceptions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Overall, two core findings can be drawn from the WTP analysis for meat labeled with the multi-level husbandry label:1. The results show that consumers are highly price sensitive and have a strong preference for low prices when buying meat: IDPs are mostly considerably above OPPs, mainly for level 4, confirming high stress regarding prices (Çolak and Koşan, 2021). Furthermore, IDPs are the prices at which the maximum share of possible buyers can be reached (Arru et al.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, two core findings can be drawn from the WTP analysis for meat labeled with the multi-level husbandry label:1. The results show that consumers are highly price sensitive and have a strong preference for low prices when buying meat: IDPs are mostly considerably above OPPs, mainly for level 4, confirming high stress regarding prices (Çolak and Koşan, 2021). Furthermore, IDPs are the prices at which the maximum share of possible buyers can be reached (Arru et al.…”
Section: Discussionmentioning
confidence: 89%
“…1. The results show that consumers are highly price sensitive and have a strong preference for low prices when buying meat: IDPs are mostly considerably above OPPs, mainly for level 4, confirming high stress regarding prices (Çolak and Kos ¸an, 2021). Furthermore, IDPs are the prices at which the maximum share of possible buyers can be reached (Arru et al, 2022), and this price can be interpreted as the perceived normal market price (Harmon et al, 2007).…”
Section: Wtp and Price Sensitivity For Label Levelsmentioning
confidence: 90%
“…Both consumer categories displayed the same positive stress price range (2.50 €) and high values of stress factors (36% and 32%), indicating that all consumers prefer and expect low prices and that the price sensitivity of the customers is high [134]. Consumers with less SK showed a slightly higher stress level, meaning a slight superior price sensitivity, i.e., they would be willing to pay around 36% less than the "normal" market price.…”
Section: Relatively Cheap Price Range and Price Thresholdsmentioning
confidence: 86%
“…In terms of consumer perception, it is a purchase activity that matches the consumer's expectations in terms of value and that the consumer evaluates as relevant and successful. Empirical analysis has shown that the indifference price (IDP) (Çolak & Koşan, 2021), which presents either the median price paid by consumers, or the price of the product of a market leader, can vary for various sub-markets as price-conscious customers (people who buy cheap products and people who buy expensive products and brands). A general price anchoring point in a market exists and many people who buy more expensive brands or product types are fully conscious of doing so (van Westendorp, 1976).…”
Section: Methodsmentioning
confidence: 99%